2013
DOI: 10.1002/cmdc.201300288
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, G‐Quadruplex Stabilisation, Docking Studies, and Effect on Cancer Cells of Indolo[3,2‐b]quinolines with One, Two, or Three Basic Side Chains

Abstract: G‐quadruplex (G4) DNA structures in telomeres and oncogenic promoter regions are potential targets for cancer therapy, and G4 ligands have been shown to modulate telomerase activity and oncogene transcription. Herein we report the synthesis and G4 thermal stabilisation effects, determined by FRET melting assays, of 20 indolo[3,2‐b]quinolines mono‐, di‐, and trisubstituted with basic side chains. Molecular modelling studies were also performed in an attempt to rationalise the ligands′ binding poses with G4. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
4
29
0
Order By: Relevance
“…Structure-activity relationships established on the basis of increased T m determined by FRET were in agreement with those previously reported for IQb series of compounds22. Based on these results compounds 2d (with one alkyldiamine side chain) and 3e (with two alkyldiamine side chains) were selected for further in vitro studies.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Structure-activity relationships established on the basis of increased T m determined by FRET were in agreement with those previously reported for IQb series of compounds22. Based on these results compounds 2d (with one alkyldiamine side chain) and 3e (with two alkyldiamine side chains) were selected for further in vitro studies.…”
Section: Discussionsupporting
confidence: 86%
“…Competition binding studies have previously shown that some small molecules can bind preferentially to quadruplex compared to triplex or duplex structures3132, and/or have differing inductive stabilization effects over G4 DNA sequences of different lengths. This is the case for those IQb compounds with 3 basic side chains in positions 7, 10 and 11, which showed higher Δ T m values for 21 mer G4-forming DNA sequences (KRAS21R, HT21, HSP90A) compared to 27 mer G4 DNA (cKit1) or longer G4 DNA structures with more complex topologies (HIF-1α)22. We report here that a small molecule can preferentially stabilize one G4 forming sequence over another with the same number of nucleotides.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations